Techno-economic Evaluation of Food Waste Fermentation for Value-added Products - Noor Intan Shafinas, Muhammad; Rosentrater, Kurt A. (MDPI AG, 2020)
Food waste (FW) is one of the most critical problems in the world. Most FW will be sent to landfills, generally accompanying some significant disadvantages to the surrounding environment. Fermentation is considered as another disposal method to deal with FW. In this study, using a techno-economic analysis (TEA) method, an evaluation of the economic impact of three different scenarios of FW fermentation is carried out. A SuperPro Designer V9.0 simulation was used to model a commercial scale processing plant for each scenario, namely, a FW fermentation process producing hydrolysis enzymes and featuring a 2-step distillation system, a FW fermentation process without enzymes, using a 2-step distillation system, and a FW fermentation process without enzymes, using a 1-step distillation system. Discounted cash flow analysis is used to estimate the minimum ethanol selling price (MESP), where the lowest MESP result of $2.41/gal ($0.64/L) of ethanol is found for the second aforementioned scenario, showing that, even without enzymes in FW fermentation, the product cost can be competitive when compared to the other scenarios considered in this study. This project thus reflects a significant positive economic impact while minimizing the environmental footprint of a commercial production facility.